Growth kinetic and characterization of Mg xZn 1-xO nanoneedles synthesized by thermal oxidation - Wongrat E. (2014)
Mg xZn 1-xO nanoneedles were synthesized on alumina substrate by using thermal oxidation technique under normal atmosphere. Zn powder and MgO powder were mixed and heated to form Mg xZn 1-xO with x content of 0-0.3 by mol at heating temperature and time of 400-1000 °C and 24 h. The morphology of Mg xZn 1-xO nanoneedle was characterized by filed emission scanning electron microscope (FE-SEM). It was found that the needle-like nanostructures with the sharp ends were observed outward from microparticles at 400-800 °C. From EDS, XRD, and TEM analysis, it was suggested that Mg xZn 1-xO alloy was formed with no segregation of MgO in Mg xZn 1-xO alloy after thermal oxidation process. Also, from reflectance spectra, the Mg xZn 1-xO nanoneedle exhibited higher energy gap than that of ZnO films for entire Mg content indicating widening band gap energy due to alloying effect. Moreover, we have proposed the growth mechanism of Mg xZn 1-xO nanoneedles based on growth kinetic of nucleation formation. This growth model can be explored to explain nanostructure of other metal-oxide alloy prepared by thermal oxidation. Copyright © 2011 American Scientific Publishers. All rights reserved.